Halide perovskite film with improved photoelectric conversion performance and preparation method and application thereof

By incorporating the novel rare earth complex Eu(tta)3phen into the precursor of perovskite solar cells, the problem of insufficient photoelectric conversion efficiency and environmental stability of perovskite solar cells is solved, and higher photovoltaic performance and better Good stability.

CN118541004BActive Publication Date: 2025-02-07SHENZHEN LANGE SEA WHALE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410509784.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2025-02-07
Estimated Expiration
2044-04-26

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of perovskite solar cells still has a lot of room for improvement from the theoretical limit value, and the environmental stability of the device is not ideal, which limits its commercial application.

Method used

A novel rare earth complex Eu(tta)3phen was incorporated into the precursor liquid of perovskite solar cells, and a halide perovskite film was prepared by anti-solvent method to improve photovoltaic performance and stability.

Benefits of technology

By doping the new rare earth complex Eu(tta)3phen, the photoelectric conversion efficiency, open circuit voltage and fill factor of perovskite solar cells is significantly improved, while improving the thermal stability and UV resistance of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118541004B_ABST
    Figure CN118541004B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of photoelectric functional materials and devices, and discloses a halide perovskite film with improved photoelectric conversion performance, a preparation method and an application thereof. The present invention uses europium chloride, 2-thenoyltrifluoroacetone containing rich functional groups (-CF3, thiophene) and 1,10-phenanthroline to synthesize a new rare earth complex Eu(tta) 3 Phen is added to the perovskite precursor solution, and finally the halide perovskite film of the present invention is prepared by the anti-solvent method. The prepared halide perovskite film is applied to perovskite solar cells, and its average photoelectric conversion performance is improved to 20.40%, and even exceeds 21% when in the best state. At the same time, it has better humidity stability, thermal stability and UV resistance, and has broad application prospects in future applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optoelectronic functional materials and devices, and specifically refers to a halide perovskite film for improving photoelectric conversion performance, and a preparation method and application thereof. Background Art

[0002] Organic-inorganic hybrid metal halide perovskites have received extensive attention and research in the field of thin-film photovoltaics in recent years due to their excellent optoelectronic properties such as low exciton binding energy, adjustable band gap, high optical absorption coefficient, high carrier mobility, long carrier diffusion length, and low-temperature solution processing.

[0003] Perovskite solar cells (PSCs), as the third generation of emerging photovoltaic technology, are one of the thin-film photovoltaic technologies with great application potential in the future. In the rapid development in the past decade, its laboratory PCE value is almost comparable to that of single-crystal Si and Si heterostructure cells, and the currently certified photoelectric conversion efficiency (PCE) has exceeded 26%. However, the PCE of PSCs still has a lot of room for improvement from the theoretical limit, and the environmental stability of the device is not ideal, which has become a bottleneck restricting its commercial application. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a halide perovskite film with improved photoelectric conversion performance and a preparation method and application thereof. The present invention uses europium chloride, 2-thiophenecarbonyl trifluoroacetone containing rich functional groups (-CF3, thiophene) and 1,10-phenanthroline to synthesize a new rare earth complex Eu(tta)3phen, and then incorporates it into the perovskite precursor solution. Finally, the halide perovskite film with improved photoelectric conversion performance of the present invention is prepared by the anti-solvent method to improve the photovoltaic performance and stability of the perovskite solar cell.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A halide perovskite film with improved photoelectric conversion performance. A new rare earth complex Eu(tta)3phen is doped during the synthesis of the halide perovskite film. The new rare earth complex Eu(tta)3phen is synthesized using europium chloride, 2-thenoyltrifluoroacetone containing rich functional groups (-CF3, thiophene), and 1,10-phenanthroline.

[0007] The present invention also proposes a method for preparing a halide perovskite film with improved photoelectric conversion performance, which specifically comprises the following steps:

[0008] S1. Prepare the raw materials required for synthesizing halide perovskite film;

[0009] S2, cleaning ITO conductive glass;

[0010] S3, preparing SnO2 electron transport layer;

[0011] S4, synthesis of a new rare earth complex Eu(tta)3phen;

[0012] S5. Prepare a Eu(tta)3phen passivated halide perovskite film, that is, a halide perovskite film with improved photoelectric conversion performance according to the present invention.

[0013] Preferably, in step S1, the raw materials required for synthesizing the halide perovskite film include commercial SnO2 aqueous sol, deionized water, europium chloride, 2-thenoyltrifluoroacetone, anhydrous ethanol, NaOH, 1,10-phenanthroline, methanol, γ-butyrolactone, lead iodide powder, methylammonium iodide, dimethyl sulfoxide and chlorobenzene.

[0014] Preferably, in step S2, the following steps are specifically included:

[0015] S2.1. Scrub the ITO conductive glass with detergent for 10 min and arrange it on a metal bracket;

[0016] S2.2, placing the ITO conductive glass treated in step S2.1 together with the metal bracket into beaker 1 containing ITO glass cleaning agent, and then placing beaker 1 in an ultrasonic cleaning machine for 20 minutes, and then taking it out and cleaning it with ultrapure water;

[0017] S2.3, placing the ITO conductive glass treated in step S2.2 together with the metal bracket into beaker 2 filled with deionized water, and then placing beaker 2 in an ultrasonic cleaning machine for 20 min, and then taking it out and cleaning it with ultrapure water;

[0018] S2.4. Place the ITO conductive glass treated in step S2.3 together with the metal bracket into beaker 3 containing anhydrous ethanol, then place beaker 3 in an ultrasonic cleaner for 20 minutes, then take it out and store it in anhydrous ethanol.

[0019] Preferably, in step S3, the following steps are specifically included:

[0020] S3.1. Take 500 μL of 15%wt commercial SnO2 hydrosol and 2000 μL of deionized water, put them into a 3 mL brown glass bottle, and stir for 4 h to obtain a SnO2 aqueous solution.

[0021] S3.2. Place the ITO conductive glass treated in step S2 into a coating machine, take 75 μL of the SnO2 solution in step S3.1, spread it evenly on the ITO conductive glass substrate, spin coat it at 3000 rpm for 30 s, then place it on a hot plate at 150°C for annealing for 30 min, and obtain the SnO2 electron transport layer after natural cooling.

[0022] Preferably, in step S4, the following steps are specifically included:

[0023] S4.1. Dissolve 91.6 mg of europium chloride and 166.6 mg of 2-thenoyltrifluoroacetone in 20.0 mL of anhydrous ethanol, and then adjust the pH to 7.0 with 1 M NaOH to obtain a mixed solution;

[0024] S4.2, stirring the mixed solution in step S4.1 in a 60°C oil bath for 1 hour, then adding 45.1 mg of 1,10-phenanthroline and continuing stirring for 5 hours, cooling to room temperature and filtering to obtain a crude product;

[0025] S4.3. The crude product in step S4.2 was recrystallized three times with methanol to obtain a pure white powder, i.e., the novel rare earth complex Eu(tta)3phen.

[0026] Preferably, in step S5, the following steps are specifically included:

[0027] S5.1. Dissolve the new rare earth complex Eu(tta)3phen in γ-butyrolactone to prepare 100 μg mL -1 A concentrated solution of

[0028] S5.2. Weigh 0.5785 g of lead iodide powder and 0.1975 g of methylammonium iodide, put them into a 5 mL brown glass bottle, use a pipette to measure 700 μL of the concentrated solution in step S5.1 and 300 μL of dimethyl sulfoxide, stir well for 6 h and then let stand for 1 h to obtain a 1 M Eu(tta)3phen-doped perovskite precursor solution;

[0029] S5.3. Weigh 75 μL of Eu(tta)3phen-doped perovskite precursor solution in step S5.2, drop it on the SnO2 electron transport layer in step S3 and spread it evenly. First, spin coat it at 2000 rpm for 15 s, then spin coat it at 4000 rpm for 60 s. When there are 35 s left, add 0.5 mL of chlorobenzene. After spin coating, anneal on a 100°C hot plate for 10 min, and cool naturally to room temperature to obtain a Eu(tta)3phen-passivated halide perovskite film, that is, the halide perovskite film with improved photoelectric conversion performance of the present invention.

[0030] The present invention also proposes an application of a halide perovskite film for improving photoelectric conversion performance. The halide perovskite film can be applied to a perovskite solar cell, thereby achieving the effect of further improving the photoelectric conversion performance of the perovskite solar cell.

[0031] The beneficial effects achieved by the present invention are as follows:

[0032] The present invention is based on the soft ion lattice characteristics of halide perovskite semiconductor materials (i.e., the preparation and crystal growth process will inevitably produce high-density defects and energy level mismatches, thereby having a negative impact on the photovoltaic performance of the battery), and from the two optimization perspectives of interface modification and active layer optimization strategy, designs and invents a halide perovskite film passivated with a new rare earth complex Eu(tta)3phen, i.e., the halide perovskite film of the present invention with improved photoelectric conversion performance.

[0033] When the new rare earth complex Eu(tta)3phen is added into the synthesis process of halide perovskite film and applied to perovskite solar cells, the new rare earth complex Eu(tta)3phen will play the following optimization role:

[0034] (1) The new rare earth complex Eu(tta)3phen can convert ultraviolet light (UV) into visible light, which is beneficial to improve the utilization rate of solar energy in perovskite solar cells and effectively prevent the photodegradation of the perovskite layer;

[0035] (2) Hydrogen bonds can be established between the organic cations of the perovskite and the -CF3 of the europium complex, which is beneficial to inhibit the release of organic cations and improve the thermal stability of the device;

[0036] (3) The thiophene group, as a Lewis base, can inhibit the formation of defects by forming coordination bonds with low-coordinated lead ions in perovskite;

[0037] (4) During the illumination and heating process, Eu in the new rare earth complex Eu(tta)3phen 3+ Pb can be oxidized 0 Converted to Pb 2+ , the generated Eu 2+ I 0 Restore to I - , thereby further inhibiting the 0 and I 0 Defects occur;

[0038] (5) The hydrophobic aromatic ring of the new rare earth complex Eu(tta)3phen is beneficial to improving the moisture resistance of the device. Under the influence of the synergistic passivation of the multifunctional groups of the new rare earth complex Eu(tta)3phen, the crystallization quality of the halide perovskite film is improved, and the energy level arrangement of the device perovskite / transport layer interface is improved, thereby significantly improving the environmental stability and UV resistance of the device.

[0039] The halide perovskite film passivated with the novel rare earth complex Eu(tta)3phenfun (i.e., the halide perovskite film with improved photoelectric conversion performance of the present invention) is applied to the perovskite solar cell, and the average photoelectric conversion efficiency of the perovskite solar cell is increased from 16.27% to 20.39%, the average open circuit voltage (VOC) is increased from 1.07 V to 1.09 V, and the average fill factor (FF) is increased from 75.18% to 80.09%. At the same time, compared with the perovskite solar cell using the undoped novel rare earth complex Eu(tta)3phenfun, the perovskite solar cell using the halide perovskite film doped with the novel rare earth complex Eu(tta)3phenfun of the present invention exhibits better thermal stability and UV resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The synthetic route of the novel rare earth complex Eu(tta)3phen in the process of preparing the halide perovskite film in Example 1 of the present invention;

[0041] Figure 2 After the halide perovskite films of Example 1 and Comparative Example 1 of the present invention are applied to the perovskite solar cell, the stability test of the anti-ultraviolet ability of the perovskite solar cell under ultraviolet light is performed;

[0042] Figure 3 This is a thermal stability test of the perovskite solar cell at a constant temperature of 85° C. after the halide perovskite films of Example 1 of the present invention and Comparative Example 1 are applied to the perovskite solar cell.

[0043] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0045] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0046] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0047] Example 1: In the synthesis process of the halide perovskite film of Example 1 of the present invention, a new rare earth complex Eu(tta)3phen is doped. The new rare earth complex Eu(tta)3phen is synthesized using europium chloride, 2-thenoyltrifluoroacetone containing rich functional groups (-CF3, thiophene) and 1,10-phenanthroline. The specific preparation steps of the halide perovskite film of Example 1 are as follows:

[0048] S1. Prepare the raw materials required for synthesizing the halide perovskite film of Example 1: commercial SnO2 aqueous sol, deionized water, europium chloride, 2-thenoyltrifluoroacetone, anhydrous ethanol, NaOH, 1,10-phenanthroline, methanol, γ-butyrolactone, lead iodide powder, methylammonium iodide, dimethyl sulfoxide and chlorobenzene;

[0049] S2, scrub the ITO conductive glass with detergent for 10 minutes, and arrange it on the metal bracket; put the scrubbed ITO conductive glass together with the metal bracket into beaker 1 filled with ITO glass cleaning agent, and then put beaker 1 in an ultrasonic cleaning machine for ultrasonic treatment for 20 minutes, then take it out and clean it with ultrapure water; put the ITO conductive glass treated in the above steps together with the metal bracket into beaker 2 filled with deionized water, and then put beaker 2 in an ultrasonic cleaning machine for ultrasonic treatment for 20 minutes, then take it out and clean it with ultrapure water; put the ITO conductive glass treated in the above steps together with the metal bracket into beaker 3 filled with anhydrous ethanol, and then put beaker 3 in an ultrasonic cleaning machine for ultrasonic treatment for 20 minutes, then take it out and store it in anhydrous ethanol;

[0050] S3, take 500 μL of 15%wt commercial SnO2 aqueous sol and 2000 μL of deionized water, put them into a 3 mL brown glass bottle, stir for 4 h, and obtain a SnO2 aqueous solution; put the ITO conductive glass treated in step S2 into a sizing machine, take 75 μL of SnO2 aqueous solution, spread it evenly on the ITO conductive glass substrate, spin coat at 3000 rpm for 30 s, then place it on a hot plate at 150°C for annealing for 30 min, and obtain a SnO2 electron transport layer after natural cooling;

[0051] S4, dissolving 91.6 mg of europium chloride and 166.6 mg of 2-thenoyltrifluoroacetone in 20.0 mL of anhydrous ethanol, and finally adjusting the pH to 7.0 with 1 M NaOH to obtain a mixed solution; stirring the mixed solution in a 60°C oil bath for 1 hour, then adding 45.1 mg of 1,10-phenanthroline and continuing stirring for 5 hours, cooling to room temperature and filtering to obtain a crude product; the crude product was recrystallized with methanol for 3 times to obtain a pure white powder, i.e., a new rare earth complex Eu(tta)3phen;

[0052] S5. Dissolve the new rare earth complex Eu(tta)3phen in step S4 in γ-butyrolactone to prepare 100 μg mL -1 concentrated solution; weigh 0.5785 g of lead iodide powder and 0.1975 g of methylammonium iodide, put them into a 5 mL brown glass bottle, use a pipette to measure 700 μL of the concentrated solution and 300 μL of dimethyl sulfoxide in turn, stir them thoroughly for 6 h and then let them stand for 1 h to obtain a Eu(tta)3phen-doped perovskite precursor solution with a concentration of 1 M; weigh 75 μL of Eu(tta)3phen-doped perovskite precursor solution, add it dropwise on the SnO2 electron transport layer in step S3 and spread it evenly, first spin coat it at 2000 rpm for 15 s, then spin coat it at 4000 rpm for 60 s, and when there are 35 s left, add 0.5 mL of chlorobenzene, and after spin coating, anneal it on a 100°C hot plate for 10 min, and naturally cool it to room temperature to obtain a Eu(tta)3phen-passivated halide perovskite film, that is, the halide perovskite film of Example 1 of the present invention.

[0053] Comparative Example 1: In the synthesis process of the halide perovskite film in Comparative Example 1 of the present invention, except that the novel rare earth complex Eu(tta)3phen is not doped, the other preparation steps are consistent with those in Example 1. The specific preparation steps of the halide perovskite film in Comparative Example 1 are as follows:

[0054] S1. Prepare the raw materials required for synthesizing the halide perovskite film of Comparative Example 1: commercial SnO2 aqueous sol, deionized water, europium chloride, 2-thenoyltrifluoroacetone, anhydrous ethanol, NaOH, 1,10-phenanthroline, methanol, γ-butyrolactone, lead iodide powder, methylammonium iodide, dimethyl sulfoxide and chlorobenzene;

[0055] S2, scrub the ITO conductive glass with detergent for 10 minutes, and arrange it on the metal bracket; put the scrubbed ITO conductive glass together with the metal bracket into beaker 1 filled with ITO glass cleaning agent, and then put beaker 1 in an ultrasonic cleaning machine for ultrasonic treatment for 20 minutes, then take it out and clean it with ultrapure water; put the ITO conductive glass treated in the above steps together with the metal bracket into beaker 2 filled with deionized water, and then put beaker 2 in an ultrasonic cleaning machine for ultrasonic treatment for 20 minutes, then take it out and clean it with ultrapure water; put the ITO conductive glass treated in the above steps together with the metal bracket into beaker 3 filled with anhydrous ethanol, and then put beaker 3 in an ultrasonic cleaning machine for ultrasonic treatment for 20 minutes, then take it out and store it in anhydrous ethanol;

[0056] S3, take 500 μL of 15%wt commercial SnO2 aqueous sol and 2000 μL of deionized water, put them into a 3 mL brown glass bottle, stir for 4 h, and obtain a SnO2 aqueous solution; put the ITO conductive glass treated in step S2 into a sizing machine, take 75 μL of SnO2 aqueous solution, spread it evenly on the ITO conductive glass substrate, spin coat at 3000 rpm for 30 s, then place it on a hot plate at 150°C for annealing for 30 min, and obtain a SnO2 electron transport layer after natural cooling;

[0057] S4. Weigh 0.5785 g of lead iodide powder and 0.1975 g of methylammonium iodide, put them into a 5 mL brown glass bottle, use a pipette to measure 700 μL of concentrated solution and 300 μL of dimethyl sulfoxide in turn, stir thoroughly for 6 h and then let stand for 1 h to obtain a 1 M Eu(tta)3phen-free perovskite precursor solution; weigh 75 μL of Eu(tta)3phen-free perovskite precursor solution, drop it on the SnO2 electron transport layer in step S3 and spread it evenly, first spin coat at 2000 rpm for 15 s, then spin coat at 4000 rpm for 60 s, and when there are 35 s left, add 0.5 mL of chlorobenzene. After spin coating, anneal on a 100°C hot plate for 10 min, and naturally cool to room temperature to obtain a halide perovskite film without Eu(tta)3phen passivation, that is, the halide perovskite film of Comparative Example 1 of the present invention.

[0058] Experimental Example: After the halide perovskite films of Example 1 and Comparative Example 1 of the present invention are applied to perovskite solar cells, the photoelectric performance test system of the perovskite solar cell is composed of a digital source meter (Keithley 2440), a simulated solar light source (AM1.5 G, 100 mW / cm 2 ), xenon lamp module (Model No. 91192, Oriel, USA) and standard silicon solar cells (91150, Newport).

[0059] In the following, the perovskite solar cell using the halide perovskite film of Example 1 is referred to as perovskite solar cell 1, and the perovskite solar cell using the halide perovskite film of Comparative Example 1 is referred to as perovskite solar cell 2.

[0060] Result analysis: Figure 1 This is the synthesis route of the new rare earth complex Eu(tta)3phen in the process of preparing the halide perovskite film in Example 1 of the present invention.

[0061] Figure 2 After the halide perovskite film of Example 1 and Comparative Example 1 of the present invention is applied to the perovskite solar cell, the stability test of the anti-ultraviolet ability of the perovskite solar cell under ultraviolet light can be observed. After 225 hours of ultraviolet light irradiation, the photoelectric conversion efficiency of the perovskite solar cell (perovskite solar cell 1) to which the halide perovskite film of Example 1 is applied is maintained at more than 70% of the initial photoelectric conversion efficiency, while the photoelectric conversion efficiency of the perovskite solar cell (perovskite solar cell 2) to which the halide perovskite film of Comparative Example 1 is applied is only maintained at 57.6% of the initial photoelectric conversion efficiency. Compared with perovskite solar cell 2, the photodegradation rate of perovskite solar cell 1 is significantly slowed down. This can be attributed to the unique down-conversion luminescence characteristics of Eu(tta)3phen. Eu(tta)3phen can convert incident ultraviolet light into visible light, enhance the ability of perovskite to resist ultraviolet rays, and extend the service life of perovskite solar cells.

[0062] Figure 3 After the halide perovskite films of Example 1 and Comparative Example 1 of the present invention were applied to perovskite solar cells, the thermal stability test of the perovskite solar cells at a constant temperature of 85°C showed that after 144 hours of heating, the perovskite solar cell (perovskite solar cell 1) using the halide perovskite film of Example 1 only lost 33% of its photoelectric conversion efficiency, and still retained the initial 43% after 225 hours. However, the perovskite solar cell (perovskite solar cell 2) using the halide perovskite film of Comparative Example 1 lost nearly 70% and completely failed after 168 hours of heating. This phenomenon can be attributed to the presence of hydrogen bonds in the device. Organic cations MA in perovskites + It can establish hydrogen bonds with -CF3 of Eu(tta)3phen compound, which is beneficial to inhibit MA + Secondly, Eu(tta)3phen produces Eu under long-term thermal stress. 2 + -Eu 3+ Redox couple, capable of simultaneous removal of I 0 and Pb 0Defects, which is one of the reasons for the improved heat resistance of the device. In addition, the thermal stability characterization of the device indirectly verifies the thermal stability of the Eu(tta)3phen additive itself, which can still be firmly anchored in the perovskite under long-term high temperature environment.

[0063] Table 1 Distribution statistics of photovoltaic performance data of perovskite solar cells

[0064]

[0065] Table 1 is a distribution statistics of photovoltaic performance data of perovskite solar cells after the halide perovskite films of Example 1 of the present invention and Comparative Example 1 are applied to perovskite solar cells. It can be observed that the average photoelectric conversion efficiency of the perovskite solar cell device using the halide perovskite film of Example 1 is increased from 16.27% to 20.39%, the average open circuit voltage (VOC) is increased from 1.07 V to 1.09 V, and the average fill factor (FF) is increased from 75.18% to 80.09%, which confirms that the addition of the new rare earth complex Eu(tta)3phen brings a qualitative improvement in the photoelectric conversion efficiency of the halide perovskite film and the perovskite solar cell.

[0066] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A halide perovskite film with improved photoelectric conversion performance, characterized in that: During the synthesis of the halide perovskite film, a rare earth complex Eu(tta)3phen is doped. The rare earth complex Eu(tta)3phen is synthesized from europium chloride, 2-thenoyltrifluoroacetone containing rich functional groups, and 1,10-phenanthroline.

2. A method for preparing a halide perovskite film with improved photoelectric conversion performance as claimed in claim 1, characterized in that: The specific steps include: S1. Prepare the raw materials required for synthesizing halide perovskite film; S2, cleaning ITO conductive glass; S3, preparing SnO2 electron transport layer; S4, synthesis of rare earth complex Eu(tta)3phen; S5. Prepare a Eu(tta)3phen passivated halide perovskite film, that is, a halide perovskite film with improved photoelectric conversion performance.

3. The method for preparing a halide perovskite film with improved photoelectric conversion performance according to claim 2, characterized in that: In step S1, the raw materials required for synthesizing the halide perovskite film include commercial SnO2 aqueous sol, deionized water, europium chloride, 2-thenoyltrifluoroacetone, anhydrous ethanol, NaOH, 1,10-phenanthroline, methanol, γ-butyrolactone, lead iodide powder, methylammonium iodide, dimethyl sulfoxide and chlorobenzene.

4. The method for preparing a halide perovskite film with improved photoelectric conversion performance according to claim 2, characterized in that: In step S2, the following steps are specifically included: S2.

1. Scrub the ITO conductive glass with detergent for 10 min and arrange it on a metal bracket; S2.2, placing the ITO conductive glass treated in step S2.1 together with the metal bracket into beaker 1 containing ITO glass cleaning agent, and then placing beaker 1 in an ultrasonic cleaning machine for 20 minutes, and then taking it out and cleaning it with ultrapure water; S2.3, placing the ITO conductive glass treated in step S2.2 together with the metal bracket into beaker 2 filled with deionized water, and then placing beaker 2 in an ultrasonic cleaning machine for 20 min, and then taking it out and cleaning it with ultrapure water; S2.

4. Place the ITO conductive glass treated in step S2.3 together with the metal bracket into beaker 3 containing anhydrous ethanol, then place beaker 3 in an ultrasonic cleaner for 20 minutes, then take it out and store it in anhydrous ethanol.

5. The method for preparing a halide perovskite film with improved photoelectric conversion performance according to claim 2, characterized in that: In step S3, the following steps are specifically included: S3.

1. Take 500 μL of 15%wt commercial SnO2 hydrosol and 2000 μL of deionized water, put them into a 3 mL brown glass bottle, and stir for 4 h to obtain a SnO2 aqueous solution. S3.

2. Place the ITO conductive glass treated in step S2 into a coating machine, take 75 μL of the SnO2 aqueous solution in step S3.1, spread it evenly on the ITO conductive glass substrate, spin coat it at 3000 rpm for 30 s, then place it on a hot plate at 150°C for annealing for 30 min, and obtain the SnO2 electron transport layer after natural cooling.

6. The method for preparing a halide perovskite film with improved photoelectric conversion performance according to claim 2, characterized in that: In step S4, the following steps are specifically included: S4.

1. Dissolve 91.6 mg of europium chloride and 166.6 mg of 2-thenoyltrifluoroacetone in 20.0 mL of anhydrous ethanol, and then adjust the pH to 7.0 with 1 M NaOH to obtain a mixed solution; S4.2, stirring the mixed solution in step S4.1 in a 60°C oil bath for 1 hour, then adding 45.1 mg of 1,10-phenanthroline and continuing stirring for 5 hours, cooling to room temperature and filtering to obtain a crude product; S4.

3. The crude product in step S4.2 was recrystallized three times with methanol to obtain a pure white powder, namely the rare earth complex Eu(tta)3phen.

7. The method for preparing a halide perovskite film with improved photoelectric conversion performance according to claim 2, characterized in that: In step S5, the following steps are specifically included: S5.

1. Dissolve the rare earth complex Eu(tta)3phen in γ-butyrolactone to prepare 100 μg mL -1 A concentrated solution of S5.

2. Weigh 0.5785 g of lead iodide powder and 0.1975 g of methylammonium iodide, put them into a 5 mL brown glass bottle, use a pipette to measure 700 μL of the concentrated solution in step S5.1 and 300 μL of dimethyl sulfoxide, stir well for 6 h and then let stand for 1 h to obtain a 1 M Eu(tta)3phen-doped perovskite precursor solution; S5.

3. Weigh 75 μL of Eu(tta)3phen-doped perovskite precursor solution in step S5.2, drop it on the SnO2 electron transport layer in step S3 and spread it evenly. First, spin coat it at 2000 rpm for 15 s, then spin coat it at 4000 rpm for 60 s. When there are 35 s left, add 0.5 mL of chlorobenzene. After spin coating, anneal on a 100°C hot plate for 10 min, and cool it naturally to room temperature to obtain a Eu(tta)3phen-passivated perovskite film, that is, a halide perovskite film with improved photoelectric conversion performance.

Citation Information

Patent Citations

  • Preparation method of europium-thenoyltrifluoroacetone infinite coordination polymer nanoparticles and film thereof

    CN108047458A

  • Light-Emitting Device and Light-Emitting Apparatus

    US20230025460A1